1998
DOI: 10.1088/0741-3335/40/9/009
|View full text |Cite
|
Sign up to set email alerts
|

Transient transport phenomena induced by cold pulses in W7-AS

Abstract: Cold-pulse experiments were carried out in the W7-AS stellarator for the first time. Carbon was injected by a laser blow-off system into the plasma edge. The electron density increase due to the injected carbon is found to be responsible for the edge electron temperature drop. In all cases, the propagation of the edge temperature perturbation to the plasma centre could be modelled with a local parameter-dependent electron heat diffusivity. Unlike in tokamaks, non-local transport effects were not observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The similarities in the nonlocal T e rise between tokamaks and LHD may suggest that the sign of the magnetic shear does not play an important role in this phenomenon. It must be noted here that the comparison between LHD and Wendelstein 7-AS ͑W7-AS͒ stellarator, in which the nonlocal T e rise has not been observed, 14 indicates that the magnetic shear itself and/or the existence of the rational values of the rotational transform at the plasma edge could be a crucial part of the nonlocal T e rise. Further investigation on this matter will be performed on LHD.…”
Section: -3mentioning
confidence: 72%
“…The similarities in the nonlocal T e rise between tokamaks and LHD may suggest that the sign of the magnetic shear does not play an important role in this phenomenon. It must be noted here that the comparison between LHD and Wendelstein 7-AS ͑W7-AS͒ stellarator, in which the nonlocal T e rise has not been observed, 14 indicates that the magnetic shear itself and/or the existence of the rational values of the rotational transform at the plasma edge could be a crucial part of the nonlocal T e rise. Further investigation on this matter will be performed on LHD.…”
Section: -3mentioning
confidence: 72%
“…Figure 5 The similarities in the nonlocal T e rise between tokamaks and LHD suggest that the sign of the magnetic shear does not play an important role in this phenomenon. The core T e rise in response to the edge cooling has not been observed in the lowshear W7-AS stellarator [35], which allows the exclusion of rational values of the rotational transform at the plasma edge. Thus the comparison between LHD and W7-AS indicates that the magnetic shear itself and/or the existence of the rational values of the rotational transform at the edge region could be a crucial part of the nonlocal T e rise.…”
Section: Characteristics Of Nonlocal T E Rise In Lhd Plasmasmentioning
confidence: 97%
“…In addition to impurity transport, preliminary measurements of heat transport of the LBI cold pulse are presented. The study of cold pulse propagation, using either laser blow-off or pellet injection, has shown that electron energy transport has a localized character in the W7-AS stellarator [6] and the RFP reversed-pinch [7], which is in contrast to the LHD stellarator [8] and to tokamaks such as TEXT [9] and JET [10] which exhibit non-local behaviours. In the TJ-II cold pulse propagation was previously studied using nitrogen puffing [11].…”
Section: Introductionmentioning
confidence: 99%